HUMAN ERROR RELATED RISKS OF MALAYSIAN LANDSLIDES - Qasim, Sadaf (World Scientific, 2011)
This paper discusses landslide risks. Rainfall is not always the major contributing factor at every landslide. Most of the times the actual root causes are engineering (e.g. flaws in slope design, errors during construction etc.) or non engineering activities (e.g. deforestation, poor vegetation cover, poor maintenance etc.). In both cases contributions of humans error to failure exists. In this paper landslide failure probabilities due to human errors have been estimated using fault tree analysis (FTA). Human errors are classified on the basis of design, construction and maintenance errors. Consequences of failure are the second basic parameter used to evaluate risks but in this study on the basis of probability of failure level of risk has been estimated. Level of risk is dependent upon the intensity of human errors involved in subtask items of design construction and maintenance. As conclusions the study furnishes probability of failure of those subtasks which are highly under the influence of human errors.